(untitled) (European Journal of Pure and Applied Mathematics, 2023)
The current paper is a trial to investigate the Eigen functions appears through mathematical treatment of 2nd kind of Fredholm integral equations by making use a new developed an Inverse Iterative Numerical Scheme (IINS). To test the applicability and accuracy of the proposed IINS, two numerical examples were solved and compared with previous results. The discussion of the results gave a good coincides up to some decimal places of results with the available ones.